Effects of Cisplatin on Superoxide Anion, Sod, Apoptosis and Cytoplasmic p21Expression in C666-1 Cell Lines Undifferentiated Nasopharyngeal Cancer - Imam Prabowo; Edi Widjajanto; Aris Widodo; Karisma Prameswari Patria Mahatmi; Handoko Nugroho Yossarsongko; Pudji Rahaju (TALENTA PUBLISHER, 2021)
Introduction: ROS, a mechanism in CIS pathogenesis, causes toxicity when cisplatin is administered. Superoxide anion (O2-), a radical anion, part of ROS that is initially triggered after a part of oxygen enters a living cell. The main principle of this enzyme is to work as a protection against oxygen toxicity and plays a role as body catalyst. The p21 has a main function in the regulation of cell cycle progression. It is able to regulate cell proliferation through its association with PCNA and DNA polymerase accessory factor as a part of cell regulation and apoptosis. Objective: To study the effects of cisplatin on the increase or decrease of O2-, SOD, proliferation (MTT), apoptosis and cytoplasmic p21 expression in C666-1 cell lines. Methods: An experimental study with a post control group design and cisplatin in group dosages of 7.86 µg/mL, 15.36 µg/mL and 30.72 µg/mL. Results: The mean difference of O2- in C666-1 cell lines between cisplatin groups was not significant (P value 0.871, P>0.05). The mean difference of SOD in C666-1 cell lines was highly significant (P value 0.001, P<0.05) showing a significant increase of SOD. The mean difference of C666-1 cell lines proliferation (MTT) between cisplatin groups was not significant (P value 0.094, P>0.05). The mean difference of C666-1 cell lines apoptosis between cisplatin groups was not significant (P value 0.104, P>0.05). Cytoplasmic p21 highest expression was found at the 30.72 dosage obtained from 24 hours observation. Conclusion: Increase of SOD after a high dose of cisplatin administration, due to the balance between ROS production and detoxification process caused by antioxidants (SOD), will affect cancer cells to proliferate and survive. Increase of apoptosis at the highest dose found in this study, showed that apoptosis was induced by cisplatin. Therefore, antioxidant administration may be considered for nasopharyngeal cancer patients.